Modernizing enterprise CMS using Pimcore : discover techniques and best practices for creating custom websites with rich digital experiences /: discover techniques and best practices for creating custom websites with rich digital experiences. (2021) - Fontani, Daniele; Guiducci, Marco; Mina, Francesco; Rietsch, Dietmar Dietz
No abstract available